Creative Thinking Ability and Collaborating in Classroom with ASICC Learning Model - ., Yusnaeni; Santoso, Agus M.; Primandiri, Poppy R; Primandiri, Poppy R; Zubaidah, Siti; K, Basri (KnE Social Sciences, 2024)
Twenty-first century education demands the birth of a generation that thinks at a higher level, including creative thinking. Apart from that it also requires the ability to collaborate. These abilities prepare students to face future challenges. Therefore, this research examines efforts to improve these two abilities in learning through quasi-experimental research using a non-equivalent pre-post test control group design by comparing two classes that program genetics courses with a total of 82 students. The experimental class was taught using the ASICC model, while the control class did not use the ASICC model. The research instrument used was an integrated essay test instrument for creative thinking abilities, while the collaboration instrument used a collaboration questionnaire. The instruments used have been validated and declared valid and reliable. The data obtained was then analyzed using the t-test, which previously began with homogeneity and normality tests. The research results showed that there were differences between the experimental class and the control class for creative thinking abilities and collaborative skills. The average collaboration value of the ASICC model class was higher than the control class. This research indicates that the ASICC learning model can be used as an alternative learning model that can improve students’ creative thinking and collaboration skills. Keywords: twenty-first century education, ASICC model, creative thinking, collaborative